Mechanism of photo-oxidation of heptafluorobutyric anhydride in the presence of NO2. Synthesis and characterization of heptafluoropropyl peroxynitrate, CF3CF2CF2OONO2 - Bossolasco, Adriana Gabriela (2012)
The photolysis of heptafluorobutyric anhydride at 254 nm in the presence of NO2 and O2 has been studied. It leads to the formation of CF3CF2CF2OONO2, CF 3CF2OONO2, and CF2O as the only fluorine-containing carbonaceous products. The formation of the new heptafluoropropyl peroxynitrate (HFPN, CF3CF2CF 2OONO2), as one of the main products, is a consequence of the formation of CF3CF2CF2OO radicals followed by the reaction with NO2. To characterize HFPN, the UV absorption cross sections and their temperature dependence between 245 and 300 K have been measured over the wavelength range 200-300 nm as well as the infrared absorption cross sections. Kinetic parameters for its thermal decomposition are also presented in the temperature range between 281 and 300 K. The Rice-Ramsperger-Kassel-Marcus calculation reveals that the rate coefficient for the thermal decomposition at 285 K is almost independent of total pressure. The mechanism for the decomposition of CF3CF2CF 2OONO2 in the presence of NO was adjusted by a kinetic model, which enabled the calculation of important rate coefficients. © 2012 American Chemical Society.